2020
DOI: 10.1111/1365-2656.13153
|View full text |Cite
|
Sign up to set email alerts
|

Predator responses to fire: A global systematic review and meta‐analysis

Abstract: Knowledge of how disturbances such as fire shape habitat structure and composition, and affect animal interactions, is fundamental to ecology and ecosystem management. Predators also exert strong effects on ecological communities, through top‐down regulation of prey and competitors, which can result in trophic cascades. Despite their ubiquity, ecological importance and potential to interact with fire, our general understanding of how predators respond to fire remains poor, hampering ecosystem management. To ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 182 publications
2
72
0
Order By: Relevance
“…These findings contrast strongly with other Australian studies that have found that variation in predation rates and fire strongly influence the abundance (rather than occurrence) of native herbivores (Dexter et al ; Foster et al ), although effects on native herbivore occurrence are less well understood. Our findings are, however, consistent with other studies that have found little influence of time‐since‐fire on fox distribution at a landscape scale (Payne et al ; Hradsky et al ) and broader trends across other predators species (Geary et al ).…”
Section: Discussionsupporting
confidence: 92%
“…These findings contrast strongly with other Australian studies that have found that variation in predation rates and fire strongly influence the abundance (rather than occurrence) of native herbivores (Dexter et al ; Foster et al ), although effects on native herbivore occurrence are less well understood. Our findings are, however, consistent with other studies that have found little influence of time‐since‐fire on fox distribution at a landscape scale (Payne et al ; Hradsky et al ) and broader trends across other predators species (Geary et al ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies about fire and biodiversity have traditionally focused on vascular plants. Other organisms, from decomposers to higher trophic levels, are only starting to be considered (Geary, Doherty, Nimmo, Tulloch, & Ritchie, 2019; Mikita‐Barbato, Kelly, & Tate, 2015; Ponisio et al., 2016). For example, fire indirectly influences ungulate populations and avian communities through its effects on habitat quality, including forage and nesting opportunities (Hutto, 2008; Rupp et al., 2006; Smucker, Hutto, & Steele, 2005).…”
Section: Effects Of Fire On Above‐ground Ecological Processesmentioning
confidence: 99%
“…Highly mobile animals in particular, have the ability to move between burned and unburned patches and therefore may respond to landscape composition, configuration and diversity at multiple scales (Rocha et al 2016;Tingley et al 2016b;Nimmo et al 2019). Limited research indicates that highly mobile animals may benefit from increased mobility and foraging opportunities afforded by fire edges (Eyes et al 2017;Vanbianchi et al 2017) but this is not consistent across species (Eby et al 2013;Geary et al 2019). Positive relationships between species richness and pyrodiversity have led to an increasing focus on managing landscapes with heterogenous burn patterns (Sitters et al 2014;Ponisio et al 2016;Tingley et al 2016b).…”
Section: Introductionmentioning
confidence: 99%